Performance Enhancement of Field-Oriented Induction Motor Control - Rizwan, Ahmad (2025)
A Master of Science thesis in Electrical Engineering by Ahmad Rizwan entitled, “Performance Enhancement of Field-Oriented Induction Motor Control”, submitted in May 2025. Thesis advisor is Dr. Rached Dhaouadi and thesis co-advisor is Dr. Habib Ur Rehman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).